2019
DOI: 10.1177/0044118x19840239
|View full text |Cite
|
Sign up to set email alerts
|

Having Less But Giving More: Work Experience and Prosocial Behavior of Chinese Working-Class Youth

Abstract: Adolescent behavior is often negatively viewed especially regarding work experience. By introducing a concept of prosocial behavior, our study attempts to provide an alternative view on the effects of teenage job and work experience. We hypothesized that work experience could generate more prosocial behaviors. By surveying a large group of working-class youth ( N = 2,860) from eight Chinese vocational schools and using structural equation modeling, we confirmed that the pattern of “having less, giving more” co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…In other words, a new ‘imagination’ of economy, as Haiven (2011) reiterates, is necessary and should be radicalised to counter the monetary logic that blocks our imaginations of economies or the actualisation of social life through reasserting a social mechanism of values through care, cooperation and solidarity, as we claim here. In this pilot study, we demonstrate how working-class students – having less but contributing more – come together to help themselves and their community (Hui, Pun, Qiu, & Koo, 2019) and potentially lay the foundation for future working-class solidarity.…”
Section: Resultsmentioning
confidence: 89%
“…In other words, a new ‘imagination’ of economy, as Haiven (2011) reiterates, is necessary and should be radicalised to counter the monetary logic that blocks our imaginations of economies or the actualisation of social life through reasserting a social mechanism of values through care, cooperation and solidarity, as we claim here. In this pilot study, we demonstrate how working-class students – having less but contributing more – come together to help themselves and their community (Hui, Pun, Qiu, & Koo, 2019) and potentially lay the foundation for future working-class solidarity.…”
Section: Resultsmentioning
confidence: 89%
“…In late October, 2017, we invited all students (approximate N = 3000) in a higher education vocational college in Xi’an, China to take part in a self-administered online survey, which is part of a large-scale research project investigating the process of “learning-to-labor” among vocational college youth in China [41,42]. A total of 1649 respondents voluntarily participated in and completed the survey without any monetary incentives (response rate = 55%).…”
Section: Methodsmentioning
confidence: 99%
“…Background variables. The questionnaire also consisted of demographic information, including respondents’ age, sex, and hukou (i.e., official household registration being rural or nonrural), which is a proxy for socioeconomic status [41]. Regarding daily gaming frequency, respondents were asked questions such as “On average how much time do you spend on gaming every day?”, and they had to choose a response from eight categories, ranging from less than one hour to seven hours or more.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have revealed that employee's past work experience can produce their pro-social behaviour including pro-environmental behaviour [7] as well as affect their personal values [8]. Employee's past work experience increase the development of their professional values in their job which lead to be more quality and ethical.…”
Section: A Employee's Past Work Experiencementioning
confidence: 99%